The Impact of Asthma Management Health Education On Asthma Knowledge and First Aid Skills - Hidayah, Isnaeni Nur; Ramdani, Meida Laely (Proceedings Series on Health & Medical Sciences, 2025)
Asthma is a chronic disease with a high prevalence, and its incidence is increasing both globally and nationally. A lack of knowledge about asthma management and first aid practices for asthma is a contributing factor to the high morbidity rates among asthma patients. Health education is expected to enhance asthma knowledge and first aid skills for individuals with asthma. To analyze the impact of asthma management health education on asthma knowledge and first aid skills. This quantitative study employed a pre-experimental design with a one-group pretest-posttest approach delivering the material through lectures and PowerPoint presentation. The study sample consisted of 36 respondents, selected using total sampling. The Wilcoxon Signed Rank Test was used for data analysis. Bivariate analysis results showed a significant difference in asthma knowledge and first aid skills before and after the health education intervention, p= 0,001. The significance level for this study was 0,05, indicating that asthma management health education significantly affects asthma knowledge and first aid practices Asthma management health education has a significant impact on improving asthma knowledge and first aid skills.